Characterization of efficiency enhancement in microchannel plate detectors - Sijbrandij, S; Cerezo, A; Deconihout, B; Godfrey, T; Smith, G (1996)
The detection efficiency of a channel-plate detector is mainly determined by the open area ratio of its input face, which is typically 60%-70%. It is known that the efficiency can be enhanced by applying an electric field normal to the channel-plate surface, such that secondary electrons generated when ions strike the channel-plate surface are returned to the detector. This paper characterises the enhancement observed in channel-plate detectors for atom probe and 3-dimensional atom probe applications. In a double channel-plate detector, it was found that improvement in efficiency was approximately 30% as compared to the situation where all secondary events are lost. The secondary electron events are found to have a broader pulse height distribution, with a mean which is a factor of three lower than that of the primary ion events. Using the variation of efficiency with grid voltage, the maximum secondary electron energy was estimated to be 10eV. This value was used to calculate the loss in time and spatial resolution which would result from the detection of secondary electrons. These effects are shown to be acceptably small within a 3-dimensional atom probe detector design, for a wide range of bias voltages. Previous work has suggested that the efficiency gain from a biassed grid drops off at grid fields in the range 25-100V/mm. This effect is shown to have been generated by field fringing effects.